2022
DOI: 10.1021/acscatal.2c00161
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Activity–Selectivity Trade-Off for Simultaneous Catalytic Elimination of Nitric Oxide and Chlorobenzene via FeVO4–Fe2O3 Interfacial Charge Transfer

Abstract: Removing chlorinated organics (chlorobenzene as a model) by a deNO x unit over a bifunctional catalyst has become the frontier of environmental catalysis. However, it is fundamentally challenging to achieve efficient selective catalytic reduction of NO x and chlorobenzene catalytic oxidation due to the trade-off between activity and selectivity. Herein, we demonstrated to break such trade-off through interfacial charge modulation on a bifunctional catalyst that is fabricated by integrating FeVO 4 and Fe 2 O 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Hence, electron density was transferred from CSO to AgO, which promotes the oxidation activity of AgO and the reduction performance of CSO with an improved balance between the NH 3 oxidation rate and the NO x reduction rate. Such an improved balance is critical for increased activity and N 2 selectivity . It has been shown that there is a negative correlation between the oxygen vacancy concentration and the work function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, electron density was transferred from CSO to AgO, which promotes the oxidation activity of AgO and the reduction performance of CSO with an improved balance between the NH 3 oxidation rate and the NO x reduction rate. Such an improved balance is critical for increased activity and N 2 selectivity . It has been shown that there is a negative correlation between the oxygen vacancy concentration and the work function.…”
Section: Resultsmentioning
confidence: 99%
“…Such an improved balance is critical for increased activity and N 2 selectivity. 63 It has been shown that there is a negative correlation between the oxygen vacancy concentration and the work function. More oxygen vacancies imply a smaller work function and easier electron spillage from the support surface.…”
Section: Stability Testingmentioning
confidence: 99%
“…NO x and dioxins are usually emitted simultaneously from stationary sources such as steel sintering, waste incineration, etc., with 1 or 2 orders of magnitude difference. The emission standards are commonly controlled strictly to ultralow limits (NO x <50 mg/Nm 3 , dioxin <0.1 ng I-TEQ/Nm 3 ) to prevent serious intimidation of human health and the ecosystem. As one of the most effective technologies in the de-NO x system, selective catalytic reduction (SCR) is widely applied in power plants and industrial boilers, in which an essential catalyst is designed to achieve a balance between surface acidity and reducibility for adsorption and activation of reductant NH 3 . For example, NH 3 prefers to be adsorbed on acid sites primarily provided by TiO 2 of the V 2 O 5 /TiO 2 catalyst and then dehydrogenates on polymeric (fast) or monomeric (slow) VO x species to yield −NH 2 intermediates to reduce NO x . ,, However, it shows low activity in catalytic oxidation of alkane/alkene, toluene, and even dioxins due to its limited reducibility. , Accordingly, it is a big challenge with great importance to reduce NO x and trace the number of dioxins simultaneously using an optimized SCR catalyst in the de-NO x system, which is named multipollutant control (MPC). …”
Section: Introductionmentioning
confidence: 99%
“…Differently, surface treatment can not only tailor the component elements on the surface of RM but also introduce metallic Fe into the Z‐Scheme heterostructures. Considering that the work function of Fe (4.8 eV) usually lies between those of TiO 2 (4.3 eV) and γ‐Fe 2 O 3 (5.5 eV), it can offer a charge flow highway for shuttling the electrons from the CB of γ‐Fe 2 O 3 to the valence band (VB) of TiO 2 [36–38] . This analogous Z‐Scheme process can be further validated by the electron spin resonance (ESR) spin‐trapping of superoxide anion radicals (⋅O 2 − ) using 5,5‐dimethyl‐1‐pyrroline N‐oxide (DMPO).…”
Section: Resultsmentioning
confidence: 96%
“…Considering that the work function of Fe (4.8 eV) usually lies between those of TiO 2 (4.3 eV) and γ-Fe 2 O 3 (5.5 eV), it can offer a charge flow highway for shuttling the electrons from the CB of γ-Fe 2 O 3 to the valence band (VB) of TiO 2 . [36][37][38] This analogous Z-Scheme process can be further validated by the electron spin resonance (ESR) spin-trapping of superoxide anion radicals ( * O 2 À ) using 5,5-dimethyl-1-pyrroline N-oxide (DMPO). Note that the CB of γ-Fe 2 O 3 is more positive than the formation potential of * O 2 À (EO 2=.O 2 À = À 0.33 V vs. NHE), no signal can be detected for Ti-PS with a possible Type II alignment (Figure 4c).…”
Section: Forschungsartikelmentioning
confidence: 95%